Unified Solution of Some Properties Related to λ-Pseudo Starlike Functions (Contemporary Mathematics, 2023)
To unify and extend the study of various subclasses of starlike and convex functions, here we introduce a new subclass of λ-pseudo starlike symmetric functions. To add more versatility to our study, we have defined a new class of functions subordinate to a conic region impacted by the well-known Janowski functions. This study extends well-known results and unifies the studies of various subclasses of α-convex functions. Coefficient estimates of the inverse function and the Fekete-Szegő result for the function class are the main results. Some interesting special cases of our main results are also presented here.
Keywords: analytic functions; bi-univalent; Fekete-Szegő; coefficient inequalities; starlike functions and convex functions; subordination